STUDI PREVALENSI DAN KARAKTERISTIK IBU BBLR DI RSUD DR. R. GOETENG TAROENADIBRATA PURBALINGGA - Ema Wahyuningrum (Universitas Harapan Bangsa Purwokerto, 2017)
Infant Low Birth Weight (LBW) is still a problem in the health sector especially perinatal health. The prevalence of LBW estimated 15% of all births in the world with limits from 3.3 to 38%. Nationally, the numbers of LBW in 2007 was 11.1% experienced a slight decline of about 10.2% in 2013. About 56% of infant deaths occurr in the neonatal and most neonatal deaths occur in 0-6 days (78.5%), mostly caused by LBW. The proportion of LBW had increased for a period of five years ie 2011-2015 increased. This study aims to determine the prevalence and characteristics of mothers who give birth with low birth weight in RSU Goeteng Taroenadibrata Purbalingga. This research is quantitative descriptive design. Sampling in this study using total sampling, which were all mothers who gave birth in category of low birth weight in RSU Goeteng Taroenadibrata Purbalingga of years 2013-2015, a number of 512 respondents. Results showed that prevalence of LBW in dr. R. Goeteng Taroenadibrata Purbalingga year 2013-2015 amounted to 16.1%, largely on the classification LBW. Prevalence of LBW is 93.2%, there is an increased prevalence of LBW in 2013-2015, most LBW occurred at the age of the mother is not at risk (20- 35 years) amounted to 73.8%, gestational age are not at risk (> 37 weeks) amounted to 51.6%, did not give birth to Gemelli 85.5%, 52.3% multiparous parity, women with complications of pregnancy amounted to 68.9%. The hospital is expected to publish policies for health workers and pregnant women about the preventive efforts of LBW. Keywords: Prevalence, Characteristics, Mother with LBW Infant